The prevalence of Api m 10 sensitization and the modification of immunotherapy in bee venom allergy - Górska, Aleksandra; Niedoszytko, Marek; Chełmińska, Marta; Kita, Karolina; Jassem, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
It is estimated that 56–94% of the adult population have been stung by a hymenopterous insect at least once in their lifetime, with one third of these cases being stung by a bee [1]. The prevalence of systemic reactions in the adult general population is 0.3–8.9% in Europe [2]. In beekeepers, this prevalence increases to 14–32% [3]. It is important to prevent any future allergic reactions based on correct diagnosis and management, including the prescription of an autoinjector with adrenaline, and specific venom immunotherapy in confirmed venom allergy [2]. Diagnosis is based on the clinical history with the classification of the type of the reaction, identification of the stinging insect and confirmation of the specific IgE-mechanism of the systemic reaction [4]. It is recommended to perform skin tests and to detect serum sIgE to insect venoms at least 2 weeks after the sting after the refractory period [1]. Although the sensitivity of serological tests with recombinant allergens is lower than traditional methods with extract allergens, molecular diagnostic approaches may improve the diagnosis accuracy in some patients excluding “false-positive” test results due to IgE directed against cross-reactive carbohydrate determinants (CCD). Furthermore, it has been recently published that negative skin test results with the Apis mellifera extract may be due to the lack of some allergens in the diagnostic and therapeutic extract [5]. Patients with a bee venom allergy often have a broad sensitisation profile with the most relevant being Api m 1, which could not be sensitised in up to 43% of cases [1, 6]. The combination of 2 allergens (Api m 1 and Api m 10) enables the diagnosis of 86.6% of cases; the combination of 6 allergens (Api m 1–5, Api m 10) has a sensitivity of 94.4% [3, 6].